Forest Restoration and Rehabilitation: A Comparative Analysis of Techniques - Krit, Pong; Chai, Napat; Kiat, Ton (Journal of Selvicoltura Asean, 2024)
Forest ecosystems are essential for biodiversity, climate regulation, and human well-being. However, deforestation and degradation threaten these vital resources, necessitating effective restoration and rehabilitation techniques. Understanding the strengths and weaknesses of various methods is crucial for improving restoration outcomes. This study aims to conduct a comparative analysis of different forest restoration and rehabilitation techniques. The objectives include evaluating their ecological effectiveness, cost-efficiency, and suitability for diverse ecological contexts. A systematic literature review was conducted, analyzing peer-reviewed articles, case studies, and reports related to various restoration techniques. Key techniques examined included natural regeneration, reforestation, afforestation, and assisted natural regeneration. Data were synthesized to highlight the comparative advantages and challenges of each method. Findings indicate that natural regeneration often yields the highest ecological success, particularly in undisturbed areas. Reforestation and afforestation techniques showed varying success rates based on species selection and site conditions. Assisted natural regeneration emerged as a cost-effective approach, promoting biodiversity while minimizing intervention. This analysis concludes that no single technique is universally applicable. Effective forest restoration requires tailored approaches that consider local ecological conditions and socio-economic factors. Policymakers and practitioners should prioritize collaborative strategies that integrate multiple techniques to enhance restoration success and ecological resilience.